Settlement of Disputed Inheritance Sale and Purchase Cases without going through PPAT in Klinting Village, Somagede District, Banyumas Regency - Soediro, Soediro; Kinanti, Wahyu Puspita; Muhammad, Mahdi (Jurnal Dinamika Hukum, 2022)
Buying and selling land has become a natural thing in Indonesia. The need for land is increasing daily along with the increase in the human population. In buying and selling land, one must pay attention to the ownership of the land, one of which is inheritance land. This study aims to determine the juridical review and legal consequences of the sale and purchase of disputed inheritance land without going through the Land Deed Maker Official (PPAT). The method used in this research is normative juridical employing library research and analyzing the applicable laws and regulations related to the legal issues under study. Before the sale and purchase transaction, the land was divided among each heir under the deed of distribution of inheritance must be ensured. Then to ensure legal certainty, the sale and purchase of the inherited land must be carried out before the PPAT. Buyers must also be careful in buying and selling inherited land by checking the juridical truth of the land data and checking directly to find out the history of land ownership from the party closest to the land's location.Keywords: Buy and Sell; Inherited Land; Land Deed Maker Official.